Effect of Vitamin D on Hormonal Factors in Women with Polycystic Ovary Syndrome (PCOS): Systematic Review and Meta-analysis - Andriana Andriana; Suharyo Hadisaputro; Aris Santjaka (Universitas STRADA Indonesia, 2021)
Women with PCOS experience hormonal disorders and vitamin D deficiency. Levels of vitamin D have a negative correlation with hormonal factors of PCOS.Analyze the effect of vitamin D on hormonal factors in PCOS.Search for articles through the Science Direct, PubMed, and Pro Quest databases. Inclusion criteria were publication with a randomized controlled trial design, women with PCOS, vitamin D intervention. The results measured were levels of LH, LH / FSH, TT, FT, SHBG, and DHEAS.12 studies were analyzed. Vitamin D significantly affected LH levels (WMD, ̶ 2.16; 95% CI, ̶ 3.87 to ̶ 0.45, P = 0.01), and LH / FSH ratio (WMD, ̶ 0.28; 95% CI, ̶ 0.38 to ̶ 0.19, P <0.00001) but did not significantly affect the levels of TT, FT, SHBG, and DHEAS.Vitamin D affects the levels of LH and LH / FSH ratio in PCOS.